2020
DOI: 10.3389/fsufs.2020.560479
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Annual Plant Diversity on Forage Productivity and Nutrition, Soil Chemistry, and Soil Microbial Communities

Abstract: Forage cover crops are gaining in popularity on the Canadian prairies, where multi-species crop mixtures are grown for soil and ecosystem enhancing benefits, but also harvested for forage. As the use of these forage mixtures increases, more knowledge is needed to understand the impact these mixtures have on forage production systems. The objective of this study was to determine the effects of increasing plant species diversity on forage productivity, soil chemistry, and soil microbial communities. Field trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Multi-species forage mixtures are becoming increasingly popular in forage production. Aside from meeting nutrient requirements of finishing cattle, high-energy mixed-species forage accumulates evenly, is highly palatable, and sustains vegetative biomass later in the growing season in comparison to perennial pastures ( Bonin and Tracy, 2012 ; Villalobos and Brummer, 2017 ; Bainard et al, 2020 ). Thus, these forages are able to support finishing growth, marbling and fat deposition, as well as carcass quality grade.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-species forage mixtures are becoming increasingly popular in forage production. Aside from meeting nutrient requirements of finishing cattle, high-energy mixed-species forage accumulates evenly, is highly palatable, and sustains vegetative biomass later in the growing season in comparison to perennial pastures ( Bonin and Tracy, 2012 ; Villalobos and Brummer, 2017 ; Bainard et al, 2020 ). Thus, these forages are able to support finishing growth, marbling and fat deposition, as well as carcass quality grade.…”
Section: Introductionmentioning
confidence: 99%
“…FUNGuild was used to parse the fungal community datasets by functional ecological guild ( Nguyen et al, 2016 ). See Bainard et al (2020) for a full description of the bioinformatics.…”
Section: Methodsmentioning
confidence: 99%
“…Peters et al (2003) have found that long-term crop rotations can increase the disease-suppressive ability of the soil and suggested changes in soil microbial communities as potential mechanisms. It has also been reported that the choice of cover crops influences the abundance of specific microbial communities (Martínez-García et al 2018;Bainard et al 2020). The recent development of high-throughput sequencing technologies allows for more detailed characterization of the soil microbial communities associated with specific crops (Bartram et al 2014;Bainard et al 2017Bainard et al , 2020Hannula et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the choice of cover crops influences the abundance of specific microbial communities (Martínez-García et al 2018;Bainard et al 2020). The recent development of high-throughput sequencing technologies allows for more detailed characterization of the soil microbial communities associated with specific crops (Bartram et al 2014;Bainard et al 2017Bainard et al , 2020Hannula et al 2020). Metagenomics, including amplicon and shotgun sequencing, of deoxyribonucleic acid (DNA) extracted from environmental samples has been used in microbiome research to study microbial communities and their interactions (Caporaso et al 2012;Schloss 2020).…”
Section: Introductionmentioning
confidence: 99%